Intermediate phenotype between CMT2Z and DIGFAN associated with a novel MORC2 variant: a case report - Kenta Hanada; Yusuke Osaki; Ryosuke Miyamoto; Kohei Muto; Shotaro Haji; Keyoumu Nazere; Yuki Kuwano; Hiroyuki Morino; Yoshiteru Azuma; Satoko Miyatake; Naomichi Matsumoto; Yuishin Izumi (Human Genome Variation)
Abstract Charcot-Marie-Tooth disease type 2Z is caused by MORC2 mutations and presents with axonal neuropathy. MORC2 mutations can also manifest as developmental delay, impaired growth, dysmorphic facies, and axonal neuropathy (DIGFAN). We report a patient exhibiting an intermediate phenotype between these diseases associated with a novel MORC2 variant. A literature review revealed that the genotype‒phenotype correlation in MORC2-related disorders is complex and that the same mutation can cause a variety of phenotypes.